“DOMINE NON SUM DIGNUS”, Filibcrto Giorgetti, F.S.C.L, 1963: a motet with both African and Latin texts; Editrice Nigrizia, via Meloncello 3/3, Bologna, Italy - Basil, Brother (International Library of African Music, 1964)
pages: 121-122
Keywords: African Music